Knowledge Sharing Practices Among Library Personnel in a University Library: A Case Study - Ogunmodede, Thomas; Bakare, Abdullahi Adewale; Rasaki, Oluwole Ejiwoye; Babarinde, Saheed Okunlola (International Journal of Knowledge Content Development & Technology, 2026)
This research delved into the dynamics of knowledge sharing within Ladoke Akintola University of Technology’s library system, focusing on specific units such as Cataloguing / Classification, Acquisition, Circulation, Reference, Virtual, and Serials Units. The study explored the challenges and opportunities associated with knowledge exchange in different functional areas, providing a comprehensive understanding of knowledge sharing dynamics within the university library context. The population comprised 55 library personnel, including professional and para-professional librarians. In addition, the research employed total enumeration sampling technique due to the small population size in order to ensure minimal sampling bias and enhanced reliability of findings. Data collection relied on a structured questionnaire designed to capture information on knowledge sharing behaviors, motivations, and channels. Moreover, the questionnaire incorporated multiple response formats and clear instructions to facilitate comprehensive data collection. Descriptive statistics was used for data analysis and the results presented in tables. The findings revealed a positive inclination towards knowledge sharing among library personnel, driven by intrinsic motivations such as personal satisfaction and a sense of achievement. External incentives such as career advancement also play a role in motivating knowledge sharing. Moreover, face-to-face interaction emerges as a predominant channel for knowledge exchange, supplemented by technological platforms such as email, mobile phones, and social media.